2018
DOI: 10.1161/jaha.118.009446
|View full text |Cite
|
Sign up to set email alerts
|

Pathoanatomic Findings Associated With Duty‐Related Cardiac Death in US Firefighters: A Case–Control Study

Abstract: BackgroundSudden cardiac death accounts for the greatest proportion of duty‐related deaths among US firefighters. Increased understanding of the pathoanatomic causes of sudden cardiac death and the risk associated with underlying cardiac pathologies is needed to develop evidence‐based screening recommendations.Methods and ResultsUsing autopsy data for duty‐related firefighter fatalities occurring between 1999 and 2014, this retrospective case–control study compared cardiac findings of male firefighters aged 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 44 publications
0
36
0
1
Order By: Relevance
“…Obesity is also associated with a procoagulatory state in the general population ( 23 , 24 ), and firefighting has been found to increase coagulatory potential in firefighters postfirefighting activity ( 25 ). Further, obesity is associated with cardiomegaly, which is a common arrhythmogenic substrate in sudden cardiac events both in the general population ( 26 ) and in firefighters ( 8 , 27 ). Previous studies among firefighters have found that higher BMI is related to unfavorable CVD risk factors, including hypertension, high total cholesterol, elevated LDL cholesterol, and low levels of HDL cholesterol ( 10 , 17 , 18 , 20 ).…”
mentioning
confidence: 99%
“…Obesity is also associated with a procoagulatory state in the general population ( 23 , 24 ), and firefighting has been found to increase coagulatory potential in firefighters postfirefighting activity ( 25 ). Further, obesity is associated with cardiomegaly, which is a common arrhythmogenic substrate in sudden cardiac events both in the general population ( 26 ) and in firefighters ( 8 , 27 ). Previous studies among firefighters have found that higher BMI is related to unfavorable CVD risk factors, including hypertension, high total cholesterol, elevated LDL cholesterol, and low levels of HDL cholesterol ( 10 , 17 , 18 , 20 ).…”
mentioning
confidence: 99%
“…A recent nationally representative sample of firefighter autopsies revealed evidence of both CAD and left ventricular hypertrophy in more than 4/5 of the cases. Cardiomegaly, coronary artery stenosis, and prior myocardial infarction were all strong independent predictors of duty-related cardiac death [92]. Swedish authorities do not keep systematic records on causes of death, but they reported that cardiovascular conditions are very rare causes of on-duty deaths [93].…”
Section: Firefighters and Cardiovascular Riskmentioning
confidence: 99%
“…Obesity may interfere with job performance and increase the risk of injury during firefighting activity 13–15. Obesity also has many deleterious effects on health indices, including reduced arterial function,16 17 glucose intolerance, dyslipidemia, type 2 diabetes, hypertension, osteoarthritis,18 low-cardiorespiratory fitness,19 pathological remodelling of the heart,20 endocrine disorders21 22 and is associated with higher all-cause mortality 23…”
Section: Introductionmentioning
confidence: 99%